COMPARISON OF HALVING THE IRRADIATION TIME OR THE VERTEPORFIN DOSE IN PHOTODYNAMIC THERAPY FOR CHRONIC CENTRAL SEROUS CHORIORETINOPATHY. Issue 12 (December 2015) - Shiode, Yusuke; Morizane, Yuki; Kimura, Shuhei; Hosokawa, Mio; Kawata, Tetsuhiro; Doi, Shinichiro; Hosogi, Mika; Fujiwara, Atsushi; Shiraga, Fumio
Abstract : Purpose: To compare the efficacy and safety of photodynamic therapy using reduced irradiation time or reduced verteporfin dose for chronic central serous chorioretinopathy. Methods: Between April 2011 and December 2013, 45 eyes with chronic central serous chorioretinopathy (43 consecutive patients) were treated with photodynamic therapy, using either half the irradiation time (18 eyes) or half the verteporfin dose (27 eyes). Outcome measures at follow-up, over at least 3 months, were complete resolution of serous retinal detachment, best-corrected visual acuity, and central retinal thickness. Results: After 3 months, serous retinal detachment had completely resolved in 88.8% of eyes in both treatment groups, which were therefore not significantly different. The logarithm of the minimal angle of resolution best-corrected visual acuity (Snellen equivalent) improved from 0.245 (20/35) to 0.130 (20/27) ( P < 0.05, paired t -test) in the reduced time group and from 0.283 (20/38) to 0.138 (20/27) ( P < 0.05) in the reduced verteporfin group. Final best-corrected visual acuities in the 2 groups were not significantly different. Central retinal thicknesses dropped from 337.0 μ m to 146.6 μ m ( P < 0.05) in the reduced time group and from 343.5 μ m to 166.9 μ m ( P < 0.05) in the reduced verteporfin group. No ocular or systemic side effects were observed. Conclusion: Reduced irradiation time and reduced verteporfin dose were equally effective and safe in photodynamic therapy for chronic central serous chorioretinopathy. Abstract : This study showed that either a reduced irradiation time or a reduced verteporfin dose in photodynamic therapy was equally effective and safe for treating chronic central serous chorioretinopathy. Reducing the photodynamic therapy irradiation time was considered to be a good treatment option in chronic central serous chorioretinopathy.